THE TRAGEDY OF DISPLACEMENT IN KASHMIR-CENTRIC HINDI NOVELS (WITH SPECIAL REFERENCE TO SHIGAF) - Kumar, Prabhakar; Bhushan, Bharat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kashmir, which is called the ’heaven on earth’, is called the ’heaven of India’ not only because of its natural beauty but also because different castes, religions and communities live together in love and harmony. Since the history of Kashmir has been a ’history of repetitions’, political instability and upheaval can be seen here from time to time. At different times in the history of Kashmir, rulers of different religions and communities ruled. Among them, many prominent people were followers of Hinduism, Buddhism and Islam.